Prognosticators of hepatocellular carcinoma with intrahepatic vascular invasion - Yuan-Chen Lo; Feng-Chun Hsu; Shih-Kai Hung; Kuo-Chih Tseng; Yu-His Hsieh; Moon-Sing Lee; Chih-Wei Tseng; Hon-Yi Lin; Liang-Cheng Chen; Wen-Yen Chiou (Tzu Chi Medical Journal)
Objective: The prognosis of intrahepatic vascular invasion, including unilateral or main portal vein tumor thrombosis (PVTT) and hepatic vein thrombosis, is still poor. Many patients with intrahepatic vascular invasions never receive radiotherapy (RT). In recent years, more conformal RT techniques such as intensity-modulated RT (IMRT) have been developed and applied to treat other cancers and have significantly improved treatment results and decreased side effects. The purpose of this study is to evaluate the treatment results in patients with intrahepatic vascular invasion and explore the role of IMRT in these treatments. Materials and Methods: There were a total of 73 patients with newly diagnosed AJCC stage IIIB hepatocellular carcinoma (HCC), with either PVTT or hepatic vein tumor thrombosis between 2007 and 2015 in our hospital. IMRT was used for all patients who received RT. Prognostic factors, including treatment modalities, liver function, and comorbidities, were analyzed using univariate and multivariate analysis with the Cox model. Survival time was analyzed using the Kaplan–Meier method. Results: The longest follow-up time was 45.3 months. The median age was 67 years. Univariate analyses indicated that IMRT, transarterial chemoembolization (TACE), target therapy (sorafenib), tumor size, Child-Pugh class, and ascites were significantly associated with overall survival (OS). In multivariate analysis, IMRT (hazard ratio [HR], 0.495; P = 0.019), sorafenib (HR, 0.340; P = 0.013), tumor size (HR, 2.085; P = 0.020), and Child-Pugh class (P = 0.004), were independent prognostic predictors for patients with intrahepatic vessel invasion, but TACE and ascites were not. The outcomes of patients who had different treatment modalities were significantly different (P < 0.001). Patients who received IMRT with TACE had the best outcomes. Patients who received an RT dose above 5400 cGy had better outcomes than those who with a dose below 5400 cGy, although the results were not significantly different (P = 0.248). Conclusion: IMRT is an important treatment component for patients with intrahepatic vascular invasion. Combined treatment modalities, such as IMRT with TACE, could improve the outcomes of HCC patients with intrahepatic vessel invasion.